Study of Religious Moderation from the Muhammadiyah Perspective: Efforts to Realize Harmony Among Indonesian Citizens - Ma’arif, Bambang Saiful; HMZ, Nandang; Faisal, Dede; ‎ , Eris (KnE Social Sciences, 2024)
Acts of violence in Indonesia often affect various other aspects of life, resulting in a loss of harmony in society and various shocks in several aspects of Indonesian society. This article aims to discuss religious moderation from Muhammadiyah’s perspective through an in-depth analysis of its basic principles and implementation. This paper is the result of research at LPPM Unisba with qualitative methods. While, the techniques are observation, interviews, and literature study. Muhammadiyah has been able to establish intense relations between citizens of different religions. The findings of this study are that Muhammadiyah is a moderate ideology that seeks to have a dialogue between text and context in the relationship between religions and nations in general. Religious Moderation in the Muhammadiyah perspective is aligned with the frame of social, national, and ummah reality. Religious moderation is not meant to reduce religious practices in order to achieve harmony. It is neither in the realm of worship, nor in the social order of nation’s citizens. Muhammadiyah has moderate opposing views in the context of multiculturalism. The update in this article is that religious moderation from the Muhammadiyah perspective does not mean abandoning the roots of Islamic teachings. But it is done selectively and functionally. Keywords: religious moderation, Muhammadiyah, interreligious dialogue, multiculturalism